Вы находитесь на странице: 1из 4

1. . 2.

.
.
f(x)
F(),
F'(x) = f(x).

F'(x) = f(x).
f(x) ,
f(x)dx - ,
const, .
:

1.

2.

3.
4

.

3. 4.
. .
:


,

,
f(x). ,
f(x)
: ,

. .
,
:

5. 6.
. .
: -
,
( 0=1).
2. 3. 4. anxn + an-1xn-1 + ... + a2x2 + a1x + a0
A, M, N, a, p, q ,
3) 4) . -
, , -.
. ,
.
. .
-,
.
-, : -
.
. ( )
-, ;
-
( ),
.
z=-;
-, -
. (
-, ),
,
,
.
z=;
.
-

7.
.
R(x)
.
Q( x)

L(x)
R( x) R(x) R( x)
. =L(x)+
Q( x) Q( x) Q( x)

A A
4 : xa ;
(xa)n
2
x + px+ q


;
Mx + N Mx + N
;
2
x + px+ q


.

.

9.
.
10. . 11.
. -
f(x) [a, b] ( ) .
- .
.

a b
.
, [a, b]
. :
-
.
:
:


1.
.
-

. .
2. F(x) f(x).
f(t) F(t),

. ,

3.

4.

5..

6.

7.

12.
.

. :


,
: ,


.
.
.